Phosphotungstic Acid Immobilized on Ionic Liquid-Modified SBA-15: Efficient Hydrophobic Heterogeneous Catalyst for Oxidative Desulfurization in Fuel - Xiong, Jun; Zhu, Wenshuai; Ding, Wenjing; Yang, Lei; Chao, Yanhong; Li, Hongping; Zhu, Fengxia; Li, Huaming (Industrial & engineering chemistry research, 2014)
A heterogeneous catalyst system was synthesized by immobilizing phosphotungstic acid on ionic liquid-modified mesoporous silica SBA-15 and applied in oxidative desulfurization. Structure and properties of catalyst were characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR), X-ray photoelectron spectroscopy (XPS), N2 adsorption–desorption, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and the contact angle. The results demonstrated that the synthesized catalyst possessed ordered mesopore structure and high special surface area. Due to the introduction of imidazole-based ionic liquid, the catalyst exhibited good wettability for model oil, which had significant contribution to desulfurization activity. Both DBT and 4,6-DMDBT could be removed completely at mild conditions (60 °C, 40 min). The removal of BT also can reach 81.3% within 60 min. Furthermore, the catalyst was recovered and reused in four reaction runs with a slight decrease in activity.